The Politics of Wellbeing Theory, Policy and Practice (Wellbeing in Politics and Policy, 2018)
This volume is the first collection in the field of wellbeing studies that places politics centre stage. Through a combination of intellectual inquiry, empirically-grounded research, and investigation across different settings, this book aims to provide fresh insights and develop new lenses through which to understand the rise and significance of the wellbeing agenda. Divided into three parts, it considers how to define wellbeing for public policy; the prospects for wellbeing as a force for political change; and the link between policy agendas and the everyday lives of people. The book explores the key political issues of power, democracy, and the legitimacy of wellbeing evidence in a range of settings - international, national and subnational/substate. The volume will appeal to wellbeing and politics scholars, as well as students and general readers with an interest in these new political agendas.